The Effect of Different Cleaning Protocols on Post Space: A SEM Study - Giuseppe Lo Giudice; Angelo Lizio; Roberto Lo Giudice; Antonio Centofanti; Giuseppina Rizzo; Michele Runci; Angela Alibrandi; Marco Cicciù (Hindawi Limited, 2016)
Aim. Purpose of the present paper is to analyze the efficiency of different post-space irrigation protocols. Methods. 28 single rooted teeth were endodontically treated. After post-space preparation every sample was assigned to one of three experimental groups and to one control group. In each group different irrigation protocols were performed as follows: EDTA (Group A), 37% orthophosphoric acid (Group B), and EDTA + 37% orthophosphoric acid with ultrasounds activation (Group C). In the control group (Group D) the irrigate association was not activated by ultrasounds. Three zones (coronal, middle, and apical) of each sample were analyzed by using Scan Electron Microscopy (SEM) without any metallization procedures. The presence of smear layer on the canal surface was qualitatively evaluated by applying Serafino's score with values included between 0 and 2. Results. The results of the research showed how Group C recorded the better results (0.81±0.72). Group A and Group B showed lower mean scores (1.06±0.69 and 1.08±0.77); Group D showed the lowest mean score of 1.30±0.69. The SEM observation analysis demonstrated how the smear layer presence decreased in the crown-apical direction. Conclusions. The different post-space treatments statistically determine significant differences on the dentinal surfaces cleansing. The absence of ultrasonic activation lowers the cleansing efficacy of endocanalar irrigants, showing sensible differences among each post-space zone.